Profile of women with ruptured ectopic pregnancy in Chitwan Medical College Teaching Hospital - Tamrakar, Renuka; Shrestha, Madhu; Paudel, Binod; Sitaula, Deekshanta (Journal of Chitwan Medical College, 2021)
Background: Ectopic pregnancy is one of the leading causes of maternal morbidity and mortality during early pregnancy. Ruptured ectopic pregnancy can be a life-threatening emergency. The aim of the present study was to know the admission rate, clinico-demographic profile and outcomes of ruptured ectopic pregnancy in Chitwan Medical College Teaching Hospital, a tertiary level hospital in Nepal. Methods: A retrospective study was conducted in Chitwan Medical College Teaching Hospital, Chitwan, Nepal. All the patients diagnosed with ruptured ectopic pregnancy were included in the study. The relevant information of patients was obtained in pre-designed pro forma. The retrospective data were entered and simple statistical analysis was done using Statistical Package for the Social Sciences version 20. Results: The rate of ruptured ectopic pregnancy was 1.69%. Mean age was 28.33 ± 5.78 years. Most of the patients presented with abdominal pain (99.0%), amenorrhea (98.0%) and bleeding per vagina (51.9%). The most common site of rupture was ampulla (50%) followed by infundibula (16.3%). The commonest associated risk factor was pelvic inflammatory disease (24%) followed by medical termination of pregnancy (19.23%), All the patients were managed surgically and there was no mortality. Conclusions: Pelvic inflammatory disease was the leading associated risk factor. Surgical management was the modality of treatment in all the cases.